A new prognostic model identifies patients aged 80 years and older with diffuse large B‐cell lymphoma who may benefit from curative treatment: A multicenter, retrospective analysis by the Spanish GELTAMO group. Issue 7 (6th May 2018) - Pardal, Emilia; Díez Baeza, Eva; Salas, Queralt; García, Tomás; Sancho, Juan M.; Monzón, Encarna; Moraleda, José M.; Córdoba, Raúl; de la Cruz, Fátima; Queizán, José A.; Rodríguez, María J.; Navarro, Belén; et al.
Abstract: The means of optimally managing very elderly patients with diffuse large B‐cell lymphoma (DLBCL) has not been established. We retrospectively analyzed 252 patients aged 80‐100 years, diagnosed with DLBCL or grade 3B follicular lymphoma, treated in 19 hospitals from the GELTAMO group. Primary objective was to analyze the influence of the type of treatment and comorbidity scales on progression‐free survival (PFS) and overall survival (OS). One hundred sixty‐three patients (63%) were treated with chemotherapy that included anthracyclines and/or rituximab, whereas 15% received no chemotherapeutic treatment. With a median follow‐up of 44 months, median PFS and OS were 9.5 and 12.5 months, respectively. In an analysis restricted to the 205 patients treated with any kind of chemotherapy, comorbidity scales did not influence the choice of treatment type significantly. Independent factors associated with better PFS and OS were: age < 86 years, cumulative illness rating scale (CIRS) score < 6, intermediate risk (1‐2) R‐IPI, and treatment with R‐CHOP at full or reduced doses. We developed a prognostic model based on the multivariate analysis of the 108 patients treated with R‐CHOP‐like: median OS was 45 vs. 12 months ( P = .001), respectively, for patients with 0‐1 vs . 2‐3 risk factors (age > 85 years, R‐IPI 3‐5 or CIRS > 5). In conclusion, treatment with R‐CHOP‐like is associated with good survival in a significant proportion of patients. We have developed a simple prognostic model that may aid the selection patients who could benefit from a curative treatment, although it needs to be validated in larger series.